The ability of a real‐time injection pressure monitoring system to discriminate between perineural and intraneural injection of the sciatic nerve in fresh cadavers. (2nd June 2018) - Saporito, A.; Quadri, C.; Capdevila, X.
Summary: Injection pressure monitoring provides valuable information to prevent intraneural injections and possibly consequent nerve damage during peripheral nerve block. However, the measurement of injection pressure along the injection line is inaccurate as it is influenced by several variables. The aim of this study was to test a new system for precise injection pressure monitoring at the needle tip in a cadaveric model. The system consists of a miniaturised pressure sensor embedded within the needle shaft that is connected via an optical fibre to an external control unit. In order to test the capacity of the system to discriminate between perineural and intraneural injections, a total of 24 ultrasound‐guided injections at various locations of the sciatic nerve (12 perineural and 12 intraneural) were performed in fresh cadavers. The injections were delivered at a constant rate by an electronic pump (5 ml saline at 10 ml.min −1 ). Two perineural and two intraneural injections were excluded from analysis, since the operator could not confirm the exact needle‐tip location. Mean (SD) peak injection pressure was significantly lower for perineural compared with intraneural injections (14 (6) kPa vs. 131 (56) kPa; p < 0.001). This study shows that this system is a reliable method to accurately monitor injection pressure at the needle tip, allowing for discrimination between perineural and intraneural injections of the sciatic nerve in fresh cadavers.